Constantine Warner Bros Pictures ; in association with Village Roadshow Pictures a Donner's Company, Batfilm Productions, Weed Road Pictures, 3 Arts Entertainment production ; directed by Francis Lawrence ; edited by Wayne Wahrman. - Lawrence, Francis; Reeves, Keanu, 1964-; Wahrman, Wayne; Weisz, Rachel, 1971-; Warner Bros. ([United States] : Warner Bros Pictures, 2005)
Basado en los personajes de Hellblazer de DC Comics/Vertigo. Constantino cuenta la historia de un detective supernatural irreverente John Constantine (Keanu Reeves), que ha estado literalmente en el infierno y en el mundo de los vivos.
DISPONIBLE
Screenplay by Kevin Brodbin and Frank Capello ; director of photography Philippe Rousselot.
Keanu Reeves, Rachel Weisz, Shia LaBeouf, Tilda Swinton, Pruitt Taylor Vince, Djimon Hounsou, Gavin Rossdale and Peter Stormare.
Adultos.
DVD.
En inglés y francés; subtitulada en inglés, francés y español.
Keywords: Aventura -- Largometraje para televisión; Horror -- Largometraje para televisión; Animación